SPE Latin American and Caribbean Petroleum Engineering Conference 2015
DOI: 10.2118/177183-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of a Gas Liquid Axial Cyclone Separator

Abstract: An experimental evaluation of a gas-liquid axial cyclone separator was conducted in a multiphase flow facilities al PDVSA-Intevep, the evaluation of the prototype was executed under controlled conditions of flow rates, between 24 and 60 Bbl/day for a liquid phase and between 80.000 and 190000 SCFD for a gas phase, considering three stator with 45°, 60° and 75° of blade angle in a swirl generator section. The axial cyclone separator was built in plexiglass in order to record with video camera the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…In 2015, J.G. Valde et al [22] conducted separation efficiency test experiments on curved inflow vanes with an inner diameter of 3 cm, an outer diameter of 5 cm, and a blade length of 5 cm at 45 • , 60 • , and 75 • and found that their separation efficiency could reach a maximum of 98% at certain gas-to-liquid ratio conditions.…”
Section: Curved Bladementioning
confidence: 99%
“…In 2015, J.G. Valde et al [22] conducted separation efficiency test experiments on curved inflow vanes with an inner diameter of 3 cm, an outer diameter of 5 cm, and a blade length of 5 cm at 45 • , 60 • , and 75 • and found that their separation efficiency could reach a maximum of 98% at certain gas-to-liquid ratio conditions.…”
Section: Curved Bladementioning
confidence: 99%
“…Another form of centrifugal separator is the axial flow separator, designed for space-constrained systems, with its central component being the guide blades. Valdez et al [19] conducted experimental assessments on curved guide blades at different inclination angles to evaluate their separation performance. The findings revealed that the maximum separation performance can surpass 0.98.…”
Section: Introductionmentioning
confidence: 99%